Analysis of Herman Goldstein Problem-Oriented Policing Awards from 1993-2017. (17th July 2018) - Schnobrich-Davis, Julie; Block, Steven; Lupacchino, Joseph
Abstract: This article analysed the finalists and winners of the Herman Goldstein Problem-Oriented Policing projects from 1993 to 2017, which provides a sample of 153 cases. The article reflects on the changes in the problem-solving process overtime in regards to the nature of crime and quality of life problems addressed, the involvement of collaborative partners, the use of technology, and the level of sophistication of the assessment phase of the Scanning, Analysis, Response, and Assessment model. The processes used by the police agencies for each step of the problem-solving model (Scan, Analyse, Respond, Assess) were reviewed. Additionally, the authors measured the amount of outside collaboration for the project from crime analysts, researchers, and stakeholders. The issue of problem-solving being a viable strategy for 21st century policing is discussed.